SlRCM1, which encodes tomato Lutescent1, is required for chlorophyll synthesis and chloroplast development in fruits - Liu, Genzhong (Hortic Res, 2021)
In plants, chloroplasts are the sites at which photosynthesis occurs, and an increased abundance of chloroplasts increases the nutritional quality of plants and the resultant color of fruits. However, the molecular mechanisms underlying chlorophyll synthesis and chloroplast development in tomato fruits remain unknown. In this study, we isolated a chlorophyll-deficient mutant, reduced chlorophyll mutant 1 (rcm1), by ethylmethanesulfonate mutagenesis; this mutant produced yellowish fruits with altered chloroplast development. MutMap revealed that Solyc08g005010 is the causal gene underlying the rcm1 mutant phenotype. A single-nucleotide base substitution in the second exon of SlRCM1 results in premature termination of its translated protein. SlRCM1 encodes a chloroplast-targeted metalloendopeptidase that is orthologous to the BCM1 protein of Arabidopsis and the stay-green G protein of soybean (Glycine max L. Merr.). Notably, the yellowish phenotype of the lutescent1 mutant can be restored with the allele of SlRCM1 from wild-type tomato. In contrast, knockout of SlRCM1 by the CRISPR/Cas9 system in Alisa Craig yielded yellowish fruits at the mature green stage, as was the case for lutescent1. Amino acid sequence alignment and functional complementation assays showed that SlRCM1 is indeed Lutescent1. These findings provide new insights into the regulation of chloroplast development in tomato fruits.